2010
DOI: 10.1111/j.1365-2915.2010.00898.x
|View full text |Cite
|
Sign up to set email alerts
|

Study ofAedes albopictusdispersal in Rome, Italy, using sticky traps in mark-release-recapture experiments

Abstract: Abstract. We report the results of three mark-release-recapture experiments carried out in an urban area in Rome, Italy, to study the active dispersal of Aedes albopictus (Diptera: Culicidae). The 4.3% recapture rate obtained supports the use of sticky traps in MRR experiments to study the dispersal of Ae. albopictus females. Most fluorescent dust-marked females were recaptured at the gravid stage at 50-200 m from the release sites during the first 9 days after release. The average of daily-MDTs (Mean Distance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
147
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(159 citation statements)
references
References 24 publications
6
147
1
1
Order By: Relevance
“…albopictus females distributed their eggs heterogeneously throughout an environment and traveled over 800m in 6 d during oviposition. Marini et al (2010), also using marked and released laboratory-reared, but bloodfed, Ae. albopictus, reported that in two of three trials, the MDT from the release location increased as days after release increased.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…albopictus females distributed their eggs heterogeneously throughout an environment and traveled over 800m in 6 d during oviposition. Marini et al (2010), also using marked and released laboratory-reared, but bloodfed, Ae. albopictus, reported that in two of three trials, the MDT from the release location increased as days after release increased.…”
Section: Discussionmentioning
confidence: 99%
“…In most studies, Ae. albopictus adults have remained in an area less than 120 m from the release site (Bonnet and Worcester 1946, Niebylski and Craig 1994, Lacroix et al 2009, Marini et al 2010); however, in some studies, this mosquito dispersed >800 m (Honorio et al 2003, Maciel-de-Freitas et al 2006. In mosquitoes that exhibit skip oviposition, little information has been reported in regards to the distance traveled between oviposition sites (Honorio et al 2003, Liew andCurtis 2004).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In its native range, the juveniles develop in water-holding tree holes and emerging adult females feed opportunistically on vertebrate species in the surrounding sylvan habitats. Limited vagility of adult mosquitoes restricts natural dispersal distances to a few hundred meters [1,2], but international trade and travel has dispersed the species well beyond its native forests of southeast Asia to urban and peri-urban landscapes throughout the Americas and Europe in the 1980s and Africa in the 1990s [3,4]. Similar to the earlier invasion by Ae.…”
Section: Introductionmentioning
confidence: 75%
“…14 However, the insufficient geographical coverage of ovitraps limits their ability to detect the invasion of dengue virus as Aedes albopictus has a short flight range of no more than 200 metres. 15 Thus, the eggs sampled in the ovitraps can only represent the mosquitoes in a confined geographic area. Nevertheless, the importance of eliminating mosquito breeding sites in our highly urbanised environment cannot be overemphasised.…”
Section: Has Dengue Found Its Home In Hong Kong?mentioning
confidence: 99%